2017
DOI: 10.1016/j.jtho.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death Ligand (PD-L1) Expression in Stage II and III Lung Adenocarcinomas and Nodal Metastases

Abstract: PD-L1 expression is associated with abundant intratumoral CD8-positive T cells in resected ADCs, suggesting a predictive role of PD-L1 expression in anti-PD-1/PD-L1 therapies; however, the possible intertumoral heterogeneity of PD-L1 expression raises a concern about selecting the most appropriate sample for PD-L1 IHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 39 publications
8
75
3
Order By: Relevance
“…In our study, we enrolled 117 LUAD patients who were diagnosed as "pan-negative" by excluding common mutations and translocations, and 104 LUAD patients who harbored one of the six gene aberrations mentioned above. It was interesting that both pan-negative and mutant patients presented low PD-L1 expression, which was significantly different from the high PD-L1 expression rate reported in previous studies (6)(7)(8)15). This result indicates that LUAD patients in East Asian population may not benefit from immunotherapy.…”
Section: Discussioncontrasting
confidence: 81%
“…In our study, we enrolled 117 LUAD patients who were diagnosed as "pan-negative" by excluding common mutations and translocations, and 104 LUAD patients who harbored one of the six gene aberrations mentioned above. It was interesting that both pan-negative and mutant patients presented low PD-L1 expression, which was significantly different from the high PD-L1 expression rate reported in previous studies (6)(7)(8)15). This result indicates that LUAD patients in East Asian population may not benefit from immunotherapy.…”
Section: Discussioncontrasting
confidence: 81%
“…7,[28][29][30] However, PD-L1 expression might differ between primary tumor and metastases as described for renal cell carcinoma and lung adenocarcinoma. [31][32][33] Therefore, it must be pointed out that a majority (57%) of tumor samples in our study was from metastatic sites, while previous studies in PC determined PD-L1 expression in the pancreatic primary. 7,[27][28][29][30] In lymphoma patients, levels of sPD-L1 have been reported to be independent of tumoral PD-L1 expression.…”
Section: Discussionmentioning
confidence: 76%
“…For example, some studies have demonstrated heterogeneity between microarray cores from the same block, whereas others have shown that although heterogeneity exists between different parts of a tumor, tumor within a single block is relatively homogeneous . In addition, 2 recent studies have demonstrated discrepancies in PD‐L1 expression between primary tumors and lymph node metastases in 30% to 38% of NSCLC cases, suggesting that tumor heterogeneity may affect PD‐L1 assessment of a tumor at different anatomical sites . The results of these studies led us to investigate whether there was a difference in the correlation of PD‐L1 expression between surgical samples and cytology samples collected from different anatomical sites compared with cytology samples collected from the same site.…”
Section: Discussionmentioning
confidence: 99%